Publishers' rights and copyright law : safeguarding access to information and media pluralism - Kowala, Michalina (Routledge, 2025)
"This book assesses the related rights of press publishers in the context of access to information and media pluralism. Discussing article15 of the Directive (EU) 2019/790 of 17 April 2019, the book looks to create balance between publishers' rights and both the protection of freedom of expression and freedom of information. With the rise of AI and an increasing focus on Internet users' rights to access information, the book focuses on online platforms and the dissemination of information as well as on the legal challenges posed by use of AI to production and dissemination of news. Using the French transposition as a case study, and referring to the implementation of art. 15 in numerous Member States, the book discusses the broad picture of the publishers' protection across the Europe and even further since international case studies in Australian and Canada are also discussed. The book will be of interest to researchers in the field of media law, EU law, copyright law and freedom of information"-- Provided by publisher.
Keywords: Copyright.; Copyright -- News articles.; Copyright -- European Union countries.; Copyright -- News articles -- European Union countries.; Publishers and publishing -- European Union countries.; Copyright -- Broadcasting rights -- European Union countries.; Authorship -- European Union countries.; Press law.; Mass media -- Law and legislation.; elektronické knihy; electronic books